Effects of the Heterogeneity of the Landscape and the Abundance of Wasmannia auropunctata on Ground Ant Assemblages in a Colombian Tropical Dry Forest - Rafael Achury; Patricia Chacón de Ulloa; Ángela Arcila (Psyche: A Journal of Entomology)
To evaluate the response of the ant assemblages to different management practices in the tropical dry forests of southwestern Colombia, 10 sites that conserve forest fragments surrounded by pastures and sugarcane crops were sampled. Tuna-fish baits placed on the ground in the three habitats captured 100 ant species (41 genera). The greatest number of species was found in the forests in contrast with a significant loss of richness and diversity in the productive habitats, the pastures being richer than the cane fields. Species richness was negatively correlated with the abundance of the little fire ant Wasmannia auropunctata. Ant species composition was related to soil temperature and percent ground cover, as well as being partially determined by location and the abundance of W. auropunctata. The forests had a significantly different species composition from the other two habitats, but there were no consistent differences between the pastures and the cane fields.